Biotransformation as a tool for remediation of polycyclic aromatic hydrocarbons from polluted environment - review on toxicity and treatment technologies. (1st February 2023) - Akash, S.; Sivaprakash, Baskaran; Rajamohan, Natarajan; Selvankumar, Thangaswamy
Abstract: Polycyclic aromatic hydrocarbons, a prominent family of persistent organic molecules produced by both anthropogenic and natural processes, are widespread in terrestrial and aquatic environments owing to their hydrophobicity, electrochemical stability and low aqueous solubility. Phenanthrene and naphthalene belong to the group of polycyclic aromatic hydrocarbons whose occurrence are reported to be relatively higher. The bioremediation mode of removing the toxicities of these two compounds has been reported to be promising than other methods. Most of the microbial classes of bacterial, fungal and algal origin are reported to degrade the target pollutants into non-toxic compounds effectively. The review aims to give an overview on toxicological studies, identification and enrichment techniques of phenanthrene and naphthalene degrading microbes and the bioremediation technologies (microbial assisted reactors, microbial fuel cells and microbial assisted constructed wetlands) reported by various researchers. All the three modes of bioremediation techniques were proved to be promising on different perspectives. In the treatment of phenanthrene, a maximum recovery of 96% and 98% was achieved in an aerobic membrane reactor with Bacillus species and single chamber air cathode microbial fuel cell with Acidovorax and Aquamicrobium respectively were reported. With the constructed wetland configuration, 95.5% of removal was attained with manganese oxide based microbial constructed wetland. The maximum degradation efficiency reported for naphthalene are 99% in a reverse membrane bioreactor, 98.5% in a marine sediment microbial fuel cell and 92.8% with a low-cost sandy soil constructed wetland. Graphical abstract: Image 1 Highlights: Bioremediation methods for removal of PAH are discussed. Overview on toxicological studies is presented. Identification and enrichment techniques degrading microbes is discussed. Future perspectives are presented.